AUTHORITY OF DISTRICT/CITY BAWASLU IN THE PROCESS OF HANDLING VIOLATIONS OF THE CODE OF ETHICS FOR AD HOC GENERAL ELECTION SUPERVISORS - Ruwiyono, Ruwiyono; Muhibbin, Moh. (Ridwan Institute, 2024)
Bawaslu as an election supervisory agency has the authority, one of which is to decide on an election violation. If you look at the process of resolving election violations, it can also be related to the concept of justice, because election violations are not a category of ordinary crimes, but extraordinary crimes whose resolution requires the concept of justice in order to realize a good democracy. The election law has contained the formulation of delix and the threat of sanctions and penalties for election violations, including the mechanism for resolving them. In a theoretical study, the conviction of a person is closely related to criminal responsibility. The focus of the discussion on legal issues is how the process of resolving election violations against the concept of justice and the implications of the decision on election violations by Bawaslu on KPU policy making. This research is a type of qualitative research. This research emphasizes on election management institutions, so the main approach used is the institutional network approach to Bawaslu, namely through a legal approach and a conceptual approach. Meanwhile, the legal material uses laws related to elections and its derivatives, namely the Bawaslu regulations in dealing with election violations. The influence of a Bawaslu decision is very important in deciding election violations, if the independence of the Bawaslu is still attached and its dignity is maintained, then the democratic process in this country will run very well and fairly for all people who want electoral justice to be realized. With the importance of an Bawaslu decision in deciding a violation, Bawaslu itself must be far from being neutral. The code of ethics as the guardian of the dignity of democracy must be strictly guarded. Revision of Law 7 of 2017 concerning Special General Elections regarding administrative sanctions against administrative violations committed by election participants and election organizers is urgently needed. The sanctions given should be clearer and firmer so that the sanctions imposed are commensurate with the type of violation committed, which in the end can serve as a deterrent so that the election organizers work according to applicable norms/rules and have a deterrent effect.